Cardiovascular Drugs and Metformin Drug Dosage According to Renal Function in Non‐Institutionalized Elderly Patients. Issue 6 (28th December 2015) - Becquemont, Laurent; Bauduceau, Bernard; Benattar‐Zibi, Linda; Al‐Salameh, Abdallah; Berrut, Gilles; Bertin, Philippe; Bucher, Sophie; Corruble, Emmanuelle; Danchin, Nicolas; Derumeaux, Geneviève; Doucet, Jean; Falissard, Bruno; et al.
Abstract: Adaptation of drug dosage to kidney function is a common problem in general practice. The aim was to describe adaptation of cardiovascular drugs and metformin according to renal function and its association with mortality with regard to metformin in a cohort of elderly patients. This was an ancillary study to the S.AGES cohort made up of patients over 65 years of age managed by their general practitioner under real‐life conditions and followed up prospectively for 3 years. The medications studied were digoxin, spironolactone and metformin. Adaptation of their daily dose according to renal function (eGFR according to CKD/EPI) was compared to that recommended in the summaries of product characteristics (SPCs) or international scientific societies (ISS). A total of 900 patients were included, including 588 on metformin. At baseline, dose adjustment according to renal function was 100% and 87.6% (95% CI: 82.6–92.6) for patients on digoxin and spironolactone respectively. For metformin, only 71.3% (95% CI: 67.6–74.9) or 78.1% (95% CI: 74.7–81.4) of patients had their dosage adapted at inclusion according to their renal function depending on whether the SPCs or ISS recommendations were considered. During the 3‐year follow‐up period, 42/588 patients died (none from lactic acidosis). At inclusion, a metformin dosage not adapted for renal function according to ISS was not associated with an increase in all‐cause mortality (OR 1.7; 95% CI 0.6–5.0, p = 0.32). In conclusion, approximately one‐quarter of elderly patients treated with metformin do not have their dosage adapted for renal function according to ISS although there is no increase in mortality after follow‐up for 3 years.